Importance of dynamic aortic evaluation in planning TEVAR - van Bogerijen, Guido H.W.; van Herwaarden, Joost A.; Conti, Michele; Auricchio, Ferdinando; Rampoldi, Vincenzo; Trimarchi, Santi; Moll, Frans L. (Annals of Cardiothoracic Surgery; Vol 3, No 3 (May 31, 2014): Type B Aortic Dissection (I), 2014)
Dynamic aortic evaluation in planning thoracic endovascular aortic repair (TEVAR) is important to provide optimal stent graft sizing. Static imaging protocols do not consider normal aortic dynamics and may lead to stent graft to aorta mismatch, causing stent graft related complications, such as type I endoleak and stent graft migration. Dynamic imaging can assist in accurate stent graft selection and sizing preoperatively, and evaluate stent graft performance during follow-up. To create new imaging technologies, integration of knowledge between diverse scientific fields is essential (i.e., engineering, informatics and medicine). Different dynamic imaging modalities, such as electrocardiographic-gated computed tomography angiography (ECGgated CTA) and four-dimensional phase-contrast MRI (4D PC-MRI), are progressively investigated and implemented into clinical practice as important instruments in preoperative planning for TEVAR. In time, further application of dynamic imaging tools for preoperative screening and follow-up after TEVAR might lead to better outcomes for patients. The advances in dynamic imaging for evaluation of the thoracic aorta with new imaging modalities and their future perspectives are addressed in this manuscript.